BUDAYA HUKUM BIAS GENDER HAKIM PENGADILAN AGAMA DALAM PERKARA CERAI TALAK - Jalaludin, Akhmad (IAIN Pekalongan, 2015)
This study depart from the reality of the attitude religious court judges in handling divorce cases. The judges attitude of gender biased is represented in the language used in court, mediation, proving even the divorce judgment of divorce cases. Factors affecting the attitude among others: educational background, culture of patriarchy, the social and family environment and gender biased laws. The gender-biased of behavior, rather than a culture of law in the Religious Court Judge, that perpetuate gender inequality in the lawless, especially in the case of divorce divorce. Kajian ini beranjak dari realitas sikap gender hakim Pengadilan Agama dalam menangani perkara cerai talak. Sikap bias gender tersebut terepresentasi dalam bahasa yang digunakan dalam persidangan, dalam mediasi, pembuktian bahkan dalam putusan perkara cerai talak. Faktor yang mempengaruhi sikap tersebut antara lain: latar belakang pendidikan, kultur patriarkhi, lingkungan sosial dan keluarga dan aturan hukum yang bias gender. Sikap bias gender hakim Pengadilan Agama tersebut, alih-alih menjadi budaya hukum di lingkungan Hakim Pengadilan Agama, sehingga melanggengkan ketidakadilan gender dalam berhukum, khususnya dalam perkara cerai talak.